2002
DOI: 10.1056/nejmoa011919
|View full text |Cite|
|
Sign up to set email alerts
|

Benefit of Atrial Pacing in Sleep Apnea Syndrome

Abstract: In patients with sleep apnea syndrome, atrial overdrive pacing significantly reduces the number of episodes of central or obstructive sleep apnea without reducing the total sleep time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
1
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(120 citation statements)
references
References 39 publications
2
103
1
14
Order By: Relevance
“…Carvedilol, a β-blocker commonly used for the treatment of CHF, has been demonstrated to reduce CSR in patients with CHF [63]. Atrial overdrive pacing was reported to reduce CSR in patients with heart failure, but these results could not be reproduced by several consecutive studies [64,65,66,67]. Cardiac resynchronization with biventricular pacemakers has repeatedly been reported to more than halve CSR in patients with severe heart failure and ventricular asynchrony.…”
Section: Treatment Of Csrmentioning
confidence: 99%
“…Carvedilol, a β-blocker commonly used for the treatment of CHF, has been demonstrated to reduce CSR in patients with CHF [63]. Atrial overdrive pacing was reported to reduce CSR in patients with heart failure, but these results could not be reproduced by several consecutive studies [64,65,66,67]. Cardiac resynchronization with biventricular pacemakers has repeatedly been reported to more than halve CSR in patients with severe heart failure and ventricular asynchrony.…”
Section: Treatment Of Csrmentioning
confidence: 99%
“…Since bradyarrhythmias are noted with apneic episodes, especially in those patients with obstructive sleep apnea, it was proposed that increasing the heart rate with atrial pacing would improve sleep disordered breathing [72]. In a preliminary study of 15 patients who had an existing pacemaker, and polysomnogram evidence of sleep apnea, Garrigue et al [72] noted that pacing at a rate 15 beats/min faster than the control night decreased the AHI.…”
Section: Cardiac Pacingmentioning
confidence: 99%
“…Reversion of OSA with CPAP or tracheostomy has been shown to abolish arrhythmia in most patients [66, 69]. Atrial overdrive pacing during sleep has been shown to reduce the number of episodes of OSA or central sleep apnea (CSA) without reducing the total sleep time [70]. Arrhythmias, especially tachyarrhythmias, may have a role in the pathogenesis of stroke by thrombus formation and embolism.…”
Section: Arrhythmiamentioning
confidence: 99%